ANALISIS PENGARUH KEBIJAKAN PEMERINTAH DAN MODAL SOSIAL TERHADAP KINERJA SOSIAL EKONOMI LEMBAGA PERKREDITAN DESA DAN KESEJAHTERAAN RUMAH TANGGA MISKIN DI KECAMATAN MENGWI KABUPATEN BADUNG - Wisudayana, Gede Putu Surya; Sudirman, I Wayan; Budiasa, I Gede Sudjana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.10.TAHUN 2018, 2018)
Study of the micro finance institution as a financial institution that serves as a companion to the poor households to become more prosperous and out of the circle of poverty can be made through a financial institution that manages to reduce the amount of poor households (Devaraja, 2011). Report Hong et al (2007) for the practice of the development of microfinance institutions in Viet Nam proves it can overthrow the number of poor households in rural. In Indonesia, the existence of micro finance institutions have contributed a very real financial access for poor households, but it is still constrained by the limited contribution of microfinance institutions Indonesia only amounted to 1.63 per cent (Siregar, 2016). The strategy of the development of microfinance institutions was described by Porter and Kramer, 2011 as the target strategy base of pyramid and the target shared value that indicates the need for microfinance institutions to build the strength of the attempt to reach the profit in berkesimbungan as well as the expansion of financial access to poor households. Goal you want to accomplish this research is to analyze the effect of social capital, Government policy and socio-economic performance of microfinance institutions against the welfare of the community.